Mucoepidermoid carcinoma of the parotid gland: Twenty‐year experience in treatment and outcomes. Issue 9 (1st May 2021) - Chan, Stephen A.; Van Abel, Kathryn M.; Lewis, Jean E.; Routman, David M.; Garcia, Joaquin J.; Karp, Emily E.; Price, Daniel L.; Janus, Jeffrey R.; Kasperbauer, Jan L.; Moore, Eric J.
Abstract: Background: Parotid gland mucoepidermoid carcinoma (MEC) has published five‐year cancer‐specific survival (CSS) rates of 77%–97%, with variance related to grade. Methods: Patients receiving primary surgery for parotid gland MEC from 1995 to 2014 at a tertiary medical center underwent clinical review, histopathologic review, and cytogenetic analysis. Survival outcomes were evaluated. Results: Among 58 patients, T/N/M classification was as follows: T1 in 35 patients, T2 in 14, T4a in 9, N0 in 53, N1 in 2, N2b in 3. Histologic grade was low in 27, intermediate in 17, and high in 12 patients with 98% MAML2 positivity. All patients underwent parotidectomy, and seven patients received adjuvant radiation therapy. CSS was 100% at 5 years and 94.1% at 10 and 15 years. Two patients experienced locoregional recurrence. Conclusions: Treatment with adequate surgical resection and adjuvant radiation therapy for high‐grade or advanced‐stage tumors yields excellent survival, independent of clinical stage or pathologic grade.